The impact of digital finance on regional carbon emission reduction capacity from the perspective of resource misallocation: Evidence from Chinese cities - Wenwen Hao; Shujun Ye; Yujin Zhang (Sustainable Futures, 2025)
The integration of financial services with technological advancements gives rise to digital finance, is instrumental in enhancing resource allocation efficiency, facilitating carbon reduction efforts, and advancing sustainable development initiatives. This study is based on panel data from 244 prefecture-level cities in China covering the period from 2011 to 2020. It employs empirical analysis to examine both the direct impact of digital finance on regional carbon emission reduction capacity and the underlying mechanisms. The results show that digital finance significantly enhances regional carbon emission reduction capacity, and this finding remains robust across a series of sensitivity tests. Furthermore, the promoting effect of digital finance exhibits a threshold effect: as digital finance matures, its marginal contribution to carbon emission reduction capacity gradually diminishes. Mechanism analysis reveals that digital finance facilitates carbon emission reduction by alleviating capital and labor misallocation at the regional level. Therefore, differentiated and dynamic digital finance development strategies should be implemented to promote digital finance services and technological innovation, accurately identify and match capital needs, develop intelligent labor matching platforms, improve labor mobility and matching efficiency, thereby driving sustainable development.